Regression analysis of the dielectric and morphological properties for porous nanohydroxyapatite/starch composites: a correlative study - Beh, Chong You; Cheng, Ee Meng; Mohd Nasir, Nashrul Fazli; Abdul Majid, Mohd Shukry; Khor, Shing Fhan; Mohd Jamir, Mohd Ridzuan; Mohd Tarmizi, Emma Ziezie; Lee, Kim Yee (MDPI, 2022)
This paper aims to investigate the dielectric properties, i.e., dielectric constant (ε′), dielectric loss factor (ε″), dielectric tangent loss (tan δ), electrical conductivity (σ), and penetration depth (Dp), of the porous nanohydroxyapatite/starch composites in the function of starch proportion, pore size, and porosity over a broad band frequency range of 5 MHz–12 GHz. The porous nanohydroxyapatite/starch composites were fabricated using different starch proportions ranging from 30 to 90 wt%. The results reveal that the dielectric properties and the microstructural features of the porous nanohydroxyapatite/starch composites can be enhanced by the increment in the starch proportion. Nevertheless, the composite with 80 wt% of starch proportion exhibit low dielectric properties (ε′, ε″, tan δ, and σ) and a high penetration depth because of its highly interconnected porous microstructures. The dielectric properties of the porous nanohydroxyapatite/starch composites are highly dependent on starch proportion, average pore size, and porosity. The regression models are developed to express the dielectric properties of the porous nanohydroxyapatite/starch composites (R2 > 0.96) in the function of starch proportion, pore size, and porosity from 1 to 11 GHz. This dielectric study can facilitate the assessment of bone scaffold design in bone tissue engineering applications.